Pengaruh Warna Kosmetik terhadap Tampilan Wajah - Mulia, Septia Puja; Muyasyaroh, Aniq; Maulida, Alfina Aprilia Hikmah; Prameswari, Tiara Agni; Anwar, Rhika Aurelia; Maghfiroh, Anik (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Cosmetic color plays a crucial role in enhancing facial appearance and shaping a person's visual and psychological impression. Choosing the right color not only serves as an aesthetic element but also influences perceptions of skin brightness, facial proportions, and individual character. This study aims to analyze the influence of cosmetic color choice on facial appearance and self-confidence. This study used a quantitative approach with a descriptive survey design. The aim was to analyze the influence of cosmetic color choice on facial appearance and self-confidence. Data were collected through a questionnaire, which was then analyzed descriptively and supported by a review of relevant literature. The survey results indicate that choosing the right cosmetic color can create a fresher, more balanced, and more harmonious facial appearance, as well as boost self-confidence. Conversely, using inappropriate colors can cause the face to appear dull and disproportionate. Therefore, understanding the influence of cosmetic color is crucial for both makeup practitioners and the general public in creating an optimal facial appearance that aligns with individual character.